2008
DOI: 10.1039/b807453d
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived (minutes) photoinduced charge separation in a structured periodic mesoporous titania containing 2,4,6-triphenylpyrylium as guest

Abstract: 2,4,6-Triphenylpyrylium (TP(+)), an electron acceptor, has been included inside the channels of two ordered mesoporous titania (mpTiO(2)). MpTiO(2) contain anatase nanoparticles (3-5 nm) templated by cetyltrimethylammonium and differ by the presence or absence of silica domains as binders of the structure. UV irradiation of TP-mpTiO(2) gives rise to a strong EPR signal. This behaviour was not observed for related materials in which TP(+) was included inside the channels of MCM-41 or the cavities of zeolite Y. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Also in the Raman spectra, big differences between low‐ and high‐T c‐TiO x are seen. By comparison with the literature data, we conclude that the low‐T c‐TiO x has anatase structure, while the high‐T c‐TiO x has rutile structure (see Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Also in the Raman spectra, big differences between low‐ and high‐T c‐TiO x are seen. By comparison with the literature data, we conclude that the low‐T c‐TiO x has anatase structure, while the high‐T c‐TiO x has rutile structure (see Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 53%
“…Also in the Raman spectra, big differences between low-and high-T c-TiO x are seen. By comparison with the literature data, [19] we conclude that the low-T c-TiO x has anatase structure, while the high-T c-TiO x has rutile structure (see Figure S2, Supporting Information). Figure 2 shows boxplots of the cell parameters of perovskite solar cells on ITO either without ETL (black), with lowtemperature processed compact-TiO x (red) or with CdS (dark yellow), respectively.…”
Section: Single Layers Of Tio X or Cds As Etlmentioning
confidence: 54%
“…53 It has been found that it is possible to excite selectively the gold surface plasmon band with visible light, and electrons expelled from the metal nanoparticles can have enough energy to move to the conduction band of the semiconductor. [54][55][56] In this way, the metal nanoparticles acting as an antenna will produce visible light sensitization of the semiconductor. 57-60 Scheme 2 shows the differences in the location of electrons and holes between the UV and visible light sensitization of the Au-TiO 2 photocatalyst.…”
Section: Doping Of Titaniamentioning
confidence: 99%
“…Different VA componentsused in variousEVA layers may be due to the need of processing, cost and performance. The pigmented-EVA shows two characteristic bands at 609 cm -1 and 446 cm -1 , assigned to the Ti-O bonds[43,44],indicatingthat rutile titanium dioxidewasused for enhancing the UV reflectivity(albedo)of the film.Additionally, the definedC=C stretching band at 1614 cm-1…”
mentioning
confidence: 99%